Sottsass 700 drawings. - Carboni, Milco, ....- (Milan : Skira, 2005)
A lifetime of drawings by Ettore Sottsass, the world-renowned architect, designer and founder of the Memphis group. This beautifully designed volume brings together 700 drawings in chronological order from 1938 to the present. The colorful collection includes studies and sketches of buildings, furniture, ceramics, glass and jewelry interspersed with more personal pages of jottings and notes and other drawings not directly linked to design or architecture illustrating the full creative range of this contemporary master. Many of the drawings have never been published before and most of them are taken from the numerous notebooks kept in Sottsass's personal archives, contributing to the very intimate, private, and personal nature of this unique publication in a sort of grand notebook of sketches that covers the entire span of his creative activity. Hans Hollein's introductory essay offers fresh insights into the work of Sottsass. Ettore Sottsass was born in Innsbruck, Austria in 1917. He received his degree in architecture from the Turin Polytechnic in 1939 and opened his first architecture and design studio in 1947. In 1958 he began working with Olivetti as a design consultant in a relationship that would last for over thirty years and win Sottsass three Compasso d'Oro prizes for design. In 1981 he founded the Memphis group, which soon became the symbol for "new design" and a point of reference for the contemporary avant-garde. One year later he founded the studio, Sottsass Associati. His works are held in the permanent collections of preeminent museums throughout the world.
Keywords: Industrieel ontwerpers